An efficient layered security framework for protecting network layer operations in mobile ad hoc networks. (1st September 2010) - Jaisankar, N.; Saravanan, R.
In mobile ad hoc networks, the nodes are dynamically changing and they have a fully decentralised topology. Hence, security is hard to achieve due to the dynamic nature of the relationships between the participating nodes as well as the vulnerabilities and limitations of the wireless transmission medium. We proposed a novel agent-based framework to monitor, detect and isolate misbehaving nodes in the MANET. The proposed framework protect both routing and data forwarding operations, which aiming to improve the efficiency in detecting and isolating misbehaving nodes with a minimum overhead. In this paper, local neighbouring nodes collaboratively monitor and sustain each other. A novel truthfulness rate strategy is introduced in each node to determine the well-behaving nodes. We evaluate through network simulations the effectiveness of the framework in detecting malicious nodes and improving the network performance.